ANALYSIS OF PRODUCTION CAPACITY AND CONSUMPTION LEVEL OF BEEF IN EAST NUSA TENGGARA PROVINCE OF INDONESIA - Jefirstson Richset Riwukore; Ahmad Yani; Asnath Maria Fuah; Luki Abdullah; Rudy Priyanto; Bagus Priyo Purwanto; Fellyanus Habaora; Yohanes Susanto (Jurnal Ilmu dan Teknologi Peternakan, 2021)
One of the livestock products that play an important role in improving food security in Indonesia is beef. Increased income, changes in consumption patterns, and population growth and increased public knowledge about nutrition affect the need for the number of cattle being slaughtered as one of the producers of meat protein in Indonesia. The purpose of this research was to determine the production capacity and consumption of beef in the province of Nusa Tenggara Timur (NTT). This research was conducted in NTT for 6 (six) months, starting from June to November 2019. This study of beef consumption is included in the case study classification. The type of data used in this study are primary and secondary data obtained from sources related to this study. Analysis of the data obtained was carried out descriptively, namely analysis carried out by way of explanation, writing, and statements that could be in the form of words (qualitative) and numbers (quantitative). Data analysis was conducted to determine the production capacity of beef cattle, beef production, and consumption of beef. The results of this study indicate that Slaughter cattle for the adequacy of consumption and domestic needs in the province of Nusa Tenggara Timur is still fulfilled for the community and in accordance with government recommendations (legislation), namely, cattle slaughtering is still below 10% of the total population of existing cattle (1,041,023 tails). Factors affecting the adequacy of domestic consumption and demand for beef in NTT, namely: (1) low purchasing power so that beef consumption is also low; (2) the community is not yet aware of the importance of animal protein (nutrition) needs for family consumption so that the level of beef consumption reaches 12% of the total protein requirement for each person; and (3) animal protein substitutions from other livestock which are cheaper affect people's thinking patterns in consuming beef.